Individual Differences in the Relative Reinforcing Effects of 3,4-Methylenedioxypyrovalerone under Fixed and Progressive Ratio Schedules of Reinforcement in Rats - Gannon, Brenda M. (J Pharmacol Exp Ther, 2017)
The recreational use of designer drugs, including synthetic cathinones (bath salts), is associated with high levels of abuse and toxicity, and represents a growing threat to public health. 3,4-Methylenedioxypyrovalerone (MDPV) is a cocaine-like monoamine uptake inhibitor, and one of the most widely available and abused synthetic cathinones. The present study used male Sprague-Dawley rats to directly compare: (1) the acquisition of responding for MDPV and cocaine under a fixed ratio (FR) 1 schedule of reinforcement; (2) full dose-response curves for MDPV and cocaine under a FR5 schedule; and (3) progressive ratio (PR) schedules of reinforcement. Self-administration of MDPV and cocaine was acquired at comparable rates, and by a similar percentage of rats. Compared with cocaine, MDPV was ∼10-fold more potent and ∼3-fold more effective at maintaining responding (PR; final ratio completed). Unlike cocaine, for which little variability was observed among rats, the FR5 dose-response curve for MDPV was shifted ∼3-fold upward for a subset of rats (high-responders) relative to other rats with identical histories (low-responders). Compared with low-responding rats, high responders also self-administered more cocaine under the FR5 schedule, and earned significantly more MDPV, cocaine, and methamphetamine under a PR schedule of reinforcement. In addition to functioning as a significantly more effective reinforcer than either cocaine or methamphetamine, MDPV also appears to be unique in its capacity to establish an enduring phenotype in rats, characterized by unusually high levels of drug intake. Although the factors underlying this high-responder phenotype are unclear, they might be related to individual differences in human drug-taking behavior.